Driving Insurance Purchase Intentions in the Digital Era: The Roles of Money Attitude, Utilitarian Motivation, and Celebrity Trustworthiness - Sabda Aji Kurniawan; Martha Racwel Patty (Universitas Muhammadiyah Sorong, 2026)
This study examines the determinants of insurance purchase intentions in the digital era by integrating perspectives from money psychology, utilitarian motivation, and celebrity trustworthiness. Using a sample of 113 followers of financial educators on Instagram, data were analyzed with PLS-SEM 4.0 to investigate the direct, indirect, and moderating effects among the proposed constructs. The findings show that money attitude significantly enhances utilitarian motivation, indicating that individuals with stronger financial orientations tend to evaluate insurance products through functional value considerations. However, utilitarian motivation does not directly influence purchase intention, nor does it mediate the link between money attitude and purchase intention, suggesting that rational assessments alone are insufficient to drive insurance decisions. Notably, celebrity trustworthiness significantly moderates the relationship between utilitarian motivation and purchase intention, demonstrating that credible public figures strengthen consumers’ confidence in the utilitarian benefits of insurance products. The study contributes to financial and digital marketing literature by highlighting the interplay between rational evaluations and source credibility. Practically, the results underscore the importance of combining functional value communication with trustworthy celebrity endorsers to enhance consumer trust and stimulate insurance purchase intentions.